FRIEDEL-CRAFTS ALKYLATION OF SUBSTITUTED BENZENES BY ALLYLDICHLOROSILANE - LEE, BW; YOO, BR; KIM, SI; JUNG, IN (AMER CHEMICAL SOC, 1994)
A Friedel-Crafts type reaction of substituted benzenes with allyldichlorosilane in the presence of aluminum chloride as a catalyst resulted in alkylation, giving 3-aryl-1,1-dichloro-1-silabutanes in good yields (60-85%). All the isomeric products derived from the alkylation were identified and the relative alkylation rates of substituted benzenes were determined by GLC. The alkylation of substituted benzenes with allyldichlorosilane at temperatures below 0-degrees-C gave ortho- and para-directing products at an early stage, but the products isomerized to the meta isomer as the reaction proceeded for prolonged times or at moderately higher reaction temperature. The competitive alkylation rates of substituted benzenes having various substituents (X) decreased in the following order: X = Ph > PhO > i-Pr > Et > Me > H > F > Cl > Br. When the alkylation rates of substituted benzenes with respect to benzene (log k(x)/k(H)) were plotted against the substituent coefficients (sigma), a good linear relationship was observed. The results showed that electron-donating groups on the benzene ring generally facilitate the alkylation, while electron-withdrawing groups are deactivating. This alkylation method is a good route to (2-arylpropyl)-dichlorosilanes having a Si-H functionality groups into the silanes.
Keywords: RESONANCE; FIELD